Feto-maternal outcome in patients with peripartum cardiomyopathy: a 5-year study in a tertiary care hospital in Kolar district - Singh, Sneha; M., Munikrishna; S. R., Sheela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Peripartum cardiomyopathy (PPCM) is a disorder of unknown cause in which initial left ventricular systolic dysfunction and symptoms of heart failure occur between the last month of pregnancy and the ﬁrst 5 months postpartum. PPCM remains a diagnosis of exclusion. There have been numerous proposed causes including hormonal abnormalities, inflammation, viral pathogens, autoimmune response, and genetic predisposition. Aim of study was to study the clinical profile, risk factors, and the management along with obstetric and perinatal outcome, in women with peripartum cardiomyopathy. Methods: This retrospective observational study was conducted on the antenatal women of age group of 18 years to 40 years, admitted in the labour ward of R. L. Jalapa hospital who presented with heart failure in last month of pregnancy till 5 months postpartum, without previously having a heart disease over the 5 year period, January 20 15 to December 2019. Results: Majority of the patients (15/18) presented with complaints of exertional dyspnoea. Mean LVEF at the time of diagnosis was 38.39%. There were 5 (27%) maternal mortality and all of them had global hypokinesia on echocardiography and presented in NYHA class III and IV. Two (11%) out of eighteen patients had intrauterine death, and all the patients who had IUFD belonged to class IV. Four babies (22.22%) had intrauterine growth restriction. Conclusions: The present study came to conclusion that in rural tertiary center, maternal outcome and prognosis was poor as patients presenting to us were majority of them in cardiogenic shock and lower LVEF in terminal stages. The associated risk factors were preeclampsia, anemia and multiple gestation which could also contribute to the poor prognosis which was noticed in the study. Early recognition of the disease is of paramount importance as the clinical manifestations can conceal and can lead to high morbidity and mortality especially within 3 months postpartum.